PENINGKATAN KUALITAS HIDUP LANSIA MELALUI PEMBERDAYAAN LANSIA PRODUKTIF, GAYA HIDUP SEHAT DAN AKTIF - Indrayogi Indrayogi; Ali Priyono; Padila Asyisya (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2022)
In nation building, health is one of the basic and important elements. Poor health conditions cause humans to be unable to regulate their own lifestyle and development in their area. As an emerging physiological syndrome in public health, frailty is a predictive factor of negative health outcomes, such as increased risk of death, decreased activities of daily living. So, in this Community Service activity, it aims to form a community that has knowledge and abilities, especially the elderly, especially in the health sector. The village that will be assisted by Community Service is Banjaransari Village, Cikijing District, Majalengka Regency, this village has more than 50 people (residents aged over 65 years) and is one of the villages with a large elderly population. The method used in this service is quantitative descriptive. The service is carried out in the form of implementing a healthy and active lifestyle: Elderly gymnastics, memory exercises and games, health education for the elderly. through how to form a healthy soul, improve the abilities and skills of the elderly, especially in Majalengka, namely Banjaransari village. The conclusion is that elderly parents have a productive spirit by doing activities to fill their spare time with physical activities such as elderly gymnastics, and making Family Medicinal Plants (Toga) in flower pots or in the yard. and set an example for the surrounding community to build their village for a better future for the nation and state. Key words: Quality of Life; Productive Old Age; Healthy and Active Lifestyle